Evaluasi Pelaksanaan Imunisasi Human Papillomavirus (HPV) Empat Puskesmas di Kota Semarang - Vania Intana Khosyi; Chriswardani Suryawati; Septo Pawelas Arso (Universitas Malahayati, 2026)
ABSTRACT Cervical cancer is one of the leading causes of death among women worldwide. WHO made a policy related to primary prevention of cervical cancer in women with Human Papillomavirus (HPV) immunization. The program targets girls aged 9-14 years or 5th and 6th grade elementary school students. Human Papillomavirus immunization is included in the BIAS immunization program implemented in schools in the puskesmas working area. The implementation of the immunization program in the puskesmas working area still has obstacles such as lack of knowledge, rejection, and hoax news circulating causing low coverage. The immunization program needs to be developed through evaluation to see how far the program is running. Therefore, this study aims to evaluate the implementation of Human Papillomavirus immunization in four puskesmas in Semarang City in 2024 using the CIPP evaluation model which is expected to provide useful information for policy makers and health workers in improving the implementation of the Human Papillomavirus immunization program. This study qualitative research conducted in the working areas of four health centers in Semarang City. Data were collected using indepth interviews with 14 informants from the Semarang City Health Office, head of puskesmas, immunization coordinators, and elementary school teachers. The results showed that the implementation of human papillomavirus immunization program is quite good. However, there are still obstacles such as vaccine logistics are still lacking, data that is not suitable, and parental rejection due to lack of knowledge. The immunization achievement of four puskesmas in Semarang City in 2024 has reached the target according to the Ministry of Health (95.5%) and the Health Office (95%). Regular evaluation and increased coordination between stakeholders are important steps to ensure the sustainability and optimization of HPV immunization programs in the future. Keywords: Immunization, HPV, Program, Puskesmas. ABSTRAK Kanker serviks salah satu penyebab kematian terbesar pada wanita yang ditemukan di dunia. WHO membuat kebijakan terkait pencegahan primer kanker serviks pada wanita dengan imunisasi Human Papillomavirus (HPV). Sasaran program anak perempuan usia 9-14 tahun atau siswi kelas 5 dan 6 Sekolah Dasar. Imunisasi Human Papillomavirus masuk kedalam program imunisasi BIAS dilaksanakan di sekolah wilayah kerja puskesmas. Pelaksanaan program imunisasi di wilayah kerja puskesmas masih terdapat kendala seperti kurangnya pengetahuan, penolakan, serta berita hoax yang beredar menyebabkan cakupan rendah. Program imunisasi perlu dikembangkan dengan melalui evaluasi untuk melihat sejauh mana program ini berjalan. Oleh karena itu, penelitian ini bertujuan untuk mengevaluasi pelaksanaan imunisasi Human Papillomavirus (HPV) empat puskesmas di Kota Semarang pada tahun 2024 dengan menggunakan model evaluasi CIPP yang diharapkan dapat memberi informasi berguna pengambilan kebijakan dan tenaga kesehatan dalam meningkatkan pelaksanaan program imunisasi Human Papillomavirus. Penelitian ini merupakan penelitian kualitatif yang dilaksanakan di wilayah kerja empat puskesmas di Kota Semarang. Pengambilan data dilakukan dengan wawancara mendalam dengan 14 informan pihak Dinas Kesehatan Kota Semarang, Kepala Puskesmas, Koordinator Imunisasi Puskesmas, serta Guru Sekolah Dasar. Hasil penelitian menunjukkan pelaksanaan program imunisasi Human Papillomavirus sudah cukup baik. Namun, masih terdapat hambatan seperti logistik vaksin masih kurang, data yang tidak sesuai,dan adanya penolakan orang tua akibat kurangnya pengetahuan. Capaian imunisasi empat puskesmas di Kota Semarang pada Tahun 2024 sudah mencapai target menurut Kemenkes (95,5%) dan Dinkes (95%). Evaluasi secara berkala dan peningkatan koordinasi antar pemangku kepentingan menjadi langkah penting untuk memastikan keberlanjutan dan optimalisasi program imunisasi HPV di masa mendatang. Kata Kunci: Imunisasi, HPV, Program, Puskesmas.